EFEKTIFITAS METODE KONSELING DALAM MENINGKATKAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI PUSKESMAS SINGGANI PALU - , Lili Suryani, Prof. dr. Djaswadi Dasuki, MPH., Sp. OG, Ph. D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: World Health Organization (WHO) demonstrates that pregnancy is a special case and needs special attention from all members of the family as a normal pregnancy may at any moment turn into an emergency condition that can result in maternal death. One cause of high maternal mortality rate is a lack of knowledge about danger signs during pregnancy. To reduce this, it is necessary to conduct counseling with efforts of high antenatal coverage that can provide an excellent opportunity to provide information, education and communication as well as counseling to women about danger signs of pregnancy. Objective: To determine the extent of the effectiveness of counseling method that specifically provided by using leaflet in improving maternal knowledge about the danger signs of pregnancy at Singgani Health Center, Palu. Methods: This was a quasi experimental study with a nonrandomized pretestposttest control group design by consecutive sampling. The number of samples was 120 respondents, namely the second trimester pregnant women. T test was used to see the mean score difference in increased maternal knowledge about the danger signs of pregnancy. Results: The analysis showed that counseling given specifically by using leaflet presented the mean value of 1.51 with a standard deviation of 1.43 while women without counseling specifically using leaflet presented the mean of 0.45 with a standard deviation of 3.37. Mean difference was 1.03 with t count equal to 2.18 and p = 0.031 or p <0.05 Conclusion: The method of counseling is provided in accordance with the standards using leaflet was effectively improving the maternal knowledge about the danger signs of pregnancy.